Peningkatan Kompetensi Guru Regnbue Preschool melalui Pelatihan Pembuatan Worksheet Digital Berbasis Canva - Mardiah MARDIAH; Anis Fitri Nur Masruriyah; Ade Hikma Tiana; Bobby Suryo Prakoso; Rizky Tito Prasetyo; Sanggi Bayu Ardika (Jurnal Pengabdian kepada Masyarakat Bidang Ilmu Komputer, 2025)
Printable worksheets are one of the learning media used in preschool or early childhood education and play an important role in stimulating children’s development. They function as effective tools to support the teaching and learning process. Interviews with teachers at Regnbue Preschool Tangerang revealed limitations in their ability to create worksheets, particularly in understanding visual design principles and using design software. In response to this issue, the community service team from the Faculty of Computer Science, UPN Veteran Jakarta, conducted a training program on developing digital worksheets using Canva, a cloud-based design application that is easy to use. Through this training, teachers were guided to understand basic visual design principles and apply them in worksheet creation. The results showed that the teachers successfully produced three printable worksheets suitable for the developmental level of preschool children, indicating that training based on simple design software can improve teachers’ competence in producing high-quality learning media.